The Impact Of External Remittances On Economic Growth In Syria - العمار, رضوان; حنا, ايناس (Latakia University Journal - Economic and Legal Sciences Series, 2022)
The research aimed to identify the impact of external remittances on Syrian economic growth in the long and short term, during the time period from 1977-2018. The study started from the following two research questions: What is the impact of external remittances on economic growth in the short term? What is the effect of external remittances on economic growth in the long run? And external transfers were considered as an independent variable, and economic growth as a dependent variable, and a controlling variable was introduced (public debt as a percentage of GDP), and annual data were used and the following tests were applied: ADF unit root test to test the stability of time series,. The study reached the most important results: There is a positive and significant effect of external transfers on economic growth in the short term in Syria. There is a positive impact of external transfers on long-term economic growth in Syria There is no effect of government debt as a controlling variable in the short term on the relationship between external transfers and economic growth. As government debt rises in the long run, the impact of external remittances on economic growth will increase.